A biomechanical comparison of the grab and conventional sprint starts in competitive swimming - Bowers, J. E.; Cavanagh, P. R. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
It was the purpose of this investigation to determine through the use of cinematographic techniques whether differences existed between the grab and conventional (circular armswing) sprint starts as used by female competitive swimmers with respect to selected velocities, angles, and temporal components. Specifically the factors investigated included: 1) the velocity of the body center of gravity at take-off; 2) the velocity of the body center of gravity at entry; 3) the angle of projection at take-off; 4) the angle of entry with respect to the water level; 5) the position of the trunk with respect to the horizontal at the point of entry; 6) the take-off time; 7) the flight time; 8) the time to a distance of 10 yards from the starting end of the pool.